2020
DOI: 10.1016/j.kint.2019.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Blocking matrix metalloproteinase-mediated syndecan-4 shedding restores the endothelial glycocalyx and glomerular filtration barrier function in early diabetic kidney disease

Abstract: Kidney International (2020) 97, 951-965; https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 80 publications
10
55
1
Order By: Relevance
“…The administration of matrix metalloproteinase inhibitors can attenuate proteinuria. MMP inhibitor treatment also significantly increased the glycocalyx depth of podocytes, but had no significant effect on glomerular-basement-membrane thickness, podocyte foot processes, and slit-diaphragm width (Ramnath et al, 2019). On the one hand, heparan sulfate fragments bind to CD44, and toll-like receptors 2 and 4 (Pahwa et al, 2016).…”
Section: Matrix Metalloproteinasesmentioning
confidence: 98%
See 1 more Smart Citation
“…The administration of matrix metalloproteinase inhibitors can attenuate proteinuria. MMP inhibitor treatment also significantly increased the glycocalyx depth of podocytes, but had no significant effect on glomerular-basement-membrane thickness, podocyte foot processes, and slit-diaphragm width (Ramnath et al, 2019). On the one hand, heparan sulfate fragments bind to CD44, and toll-like receptors 2 and 4 (Pahwa et al, 2016).…”
Section: Matrix Metalloproteinasesmentioning
confidence: 98%
“…Diabetes triggers the release of inflammatory factors. Previous research indicated that, on the surface of the glomerular vascular endothelium (Yuelong et al, 2014), proinflammatory factors such as TNF-α activate mast cells and cause them to release enzymes (hyaluronidase, heparinase, MMP-9/2) (Ramnath et al, 2019;Reine et al, 2019). Then, MMP-9 can destroy the glycocalyx, and release heparan sulfate and syndecan into the blood (Ramnath et al, 2014).…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…ROS also decrease the levels of the tissue inhibitors of metalloproteinases (TIMPs), thereby increasing the activity of MMPs ( Siwik and Colucci, 2004 ). The inhibition of MMPs was able to restore the shedding of syndecan-4 in early diabetic disease ( Ramnath et al, 2020 ).…”
Section: Effect Of Ros On Endothelial Glycocalyx Degradationmentioning
confidence: 99%
“…It should be noted that MMP-mediated shedding of syndecans has been found to contribute to the endothelial glycocalyx disruption as occurs in various entities, including diabetes mellitus and other pro-inflammatory states [ 80 , 81 ]. Additionally, bilateral renal IRI in syndecan-1–deficient mice as compared to wild-type mice has been associated with augmented macrophage and myofibroblast numbers as well as tubular injury [ 82 ].…”
Section: Iri and Glycocalyx Damage In Kidney Transplantationmentioning
confidence: 99%
“…GAG chains of syndecan-1 act as binding sites for hepatocyte growth factor (HGF), and mediate HGF interaction with its specific receptor, the mesenchymal epithelial transition factor (c-Met). In turn, HGF receptor together with its downstream effectors, AKT and glycogen synthase kinase-3β (GSK-3β) have been shown to play a renoprotective role in AKI [ 81 , 84 ]. Pharmacological inhibition of syndecan-1 shedding in the setting of IRI activates phosphorylation of the c-Met/AKT/GSK-3β signaling pathway, thus further supporting the important role of syndecan-1 as a coreceptor for HGF to attenuate apoptosis and inflammation in IRI [ 85 ].…”
Section: Iri and Glycocalyx Damage In Kidney Transplantationmentioning
confidence: 99%